Comparative Efficacy of Ultrasound and Laser Therapy in Modulating Inflammatory Markers in a Rat Model of Testicular Inflammation: Study of US & LLLT on CRP in rats orchitis - Abdelkader, Ahmed Mamdouh; Torad, Ahmed Ali; Elbedewy, Mohamed Ahmed; Mostafa, Nihal; Shalaby, Amr Saadeldeen Mohamed; Abdeldayem, Tayseer Saber; Ahmed, Alaa Anwar (Journal of Lasers in Medical Sciences, 2025)
Introduction: All three degrees of inflammation (cellular, tissue, and systemic) are normal reactions that our bodies have to foreign substances. Cellular damage from bacteria, viruses, and even cancer can be warded off with the aid of these reactions. An efficient non-pharmaceutical method of treating inflammation is frequently seen as physiotherapy. In this study, the effects of ultrasonic treatment (US) and low-level laser therapy (LLLT) on the levels of C-reactive protein (CRP) in rats with inflamed testicles are investigated. Methods: Three groups, each including eighteen male rats, were established: the control group (C), the US group (which received ultrasonic treatment), and the LLLT group (which received low-level laser therapy). Results: The blood CRP levels in the US group were significantly lower than those in the control and LLLT groups. Conclusion: Findings suggest that ultrasound might be more effective than LLLT in treating testicular inflammation, as shown by the decrease in blood CRP levels.